2018
DOI: 10.1021/acsenergylett.8b00121
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of Grain Boundaries by Phenethylammonium in Formamidinium-Methylammonium Lead Halide Perovskite Solar Cells

Abstract: In this work, we report the benefits of incorporating p h e n e t h y l a m m o n i u m c a t i o n ( P E A + ) i n t o ( H C -(NH 2 ) 2 PbI 3 ) 0.85 (CH 3 NH 3 PbBr 3 ) 0.15 perovskite for the first time. After adding small amounts of PEA cation (<10%), the perovskite film morphology is changed but, most importantly, grain boundaries are passivated. This is supported by Kelvin Probe Force Microscopy (KPFM). The passivation results in the increase in photoluminescence intensity and carrier lifetimes of test st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
282
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(292 citation statements)
references
References 38 publications
9
282
1
Order By: Relevance
“…Grancini et al proposed that the addition of 3 mol% of 5‐aminovaleric acid (5‐AVA) into MAPbI 3 based n–i–p devices resulted in a 2D/3D interface at the perovskite–metal oxide interface . In planar devices, several reports suggest bulky cations are possibly located at grain surfaces or boundaries, however in the literature no direct evidence to support these claims has been presented . Given the size of NMA we consider the molecule is too large to be incorporated into the bulk of MAPbI 3 , without at least causing significant structural distortion (XRD data shown in Figure S2a, Supporting Information).…”
Section: Resultsmentioning
confidence: 92%
“…Grancini et al proposed that the addition of 3 mol% of 5‐aminovaleric acid (5‐AVA) into MAPbI 3 based n–i–p devices resulted in a 2D/3D interface at the perovskite–metal oxide interface . In planar devices, several reports suggest bulky cations are possibly located at grain surfaces or boundaries, however in the literature no direct evidence to support these claims has been presented . Given the size of NMA we consider the molecule is too large to be incorporated into the bulk of MAPbI 3 , without at least causing significant structural distortion (XRD data shown in Figure S2a, Supporting Information).…”
Section: Resultsmentioning
confidence: 92%
“…By conducting a controlled trial of aniline, benzylamine, and phenethylamine, Wang et al indicated that devices' better moisture resistance was owing to the hydrophobicity of the phenyl group (Figure f) . However, the insulation of PEAI and the possible deterioration of light absorption make the J SC and FF of the device worse . Besides, Zhao et al grew a 4‐fluoroaniline (FAL) passivation layer by vapor post‐treatment (Figure e), the conjugated amine in aromatic ring and para ‐fluorine substituent facilitate both defect passivation and charge transfer .…”
Section: Passivation Of Perovskite Layermentioning
confidence: 99%
“…[14,59] For the most high-efficient PSCs, however, they commonly contain both ETL and HTL to efficiently collect [42] one kind of charge while blocking the other kind to avoid carrier recombination thus high performance can be ensured. [65] In ETL-free PSCs of regular-structured, Liu et al reported the ETLfree PSC with the high PCE of 13.5% in 2014. [65] In ETL-free PSCs of regular-structured, Liu et al reported the ETLfree PSC with the high PCE of 13.5% in 2014.…”
Section: Etl-free and Htl-free Planar Pscsmentioning
confidence: 99%
“…They raised the Voc from 0.99 V to 1.1 V. [65] Meanwhile, Snaith et al added n-butylammonium iodide(BAI) into a mixedcation lead mixed-halide FA 0.83 Cs 0.17 Pb(I y Br 1 À y ) 3 -based perovskite, and a PCE of 20.6% was achieved. For example, Ho-Baillie et al incorporated a small amount of phenethylammonium cation (PEA + ) i n t o ( H C (NH 2 ) 2 PbI 3 ) 0.85 (CH 3 NH 3 PbBr 3 ) 0.15 -based perovskite to passivated grain boundaries.…”
Section: Bulk Passivation By Organic Molecularmentioning
confidence: 99%